Development of an Interactive Android-Based Ayo-Olopon Game - Bolaji Abigail Omodunbi; Afeez Adekunle Soladoye; Opeyemi Asaolu; Emmanuel Yusuf (ABUAD Journal of Engineering Research and Development)
One of the most widely acceptable means of entertainment all over the world is Games especially in Africa to ease the mind from stress after a rigorous day’s work. Over the years, there have been several African games nearly going into extinction due to the advancement of more new smartphone-based games and the general public is more comfortable using the modern-day gizmo. This has brought about reduction in the number of people that understands and knows about African traditional games and ethics. A lot of effort has been put in place by many developers and researchers to digitalize these games (like Ayo-Olopon) to improve their popularity and expand their accessibility across the globe. The current versions of this Ayo-Olopon game does not provide room for Multi-player in real time nor presence of third party as viewer during the game session. This research developed an android-based Ayo-Olopon game using a stack of React Native for the frontend design and server-side scripting through Node.Js, Websocket was also incorporated which enables real-time communication for multi-players and a third party to join the game as a viewer. The game was evaluated using feedback from randomly selected user and more than 98% of them ascertained its uniqueness and excellent performance. Response speed and transfer time were also used as the evaluation metrics with varying network technologies and protocols, WLAN network technology with gave the shortest response time and transfer speed of 150ms and 0.263s respectively f. This shows that the developed Ayo-olopon game gave a very satisfactory user experience and good performance with good Computational time. Future work should focus on enabling viewers to use audio or chat to motivate the players and increase their morale.